THE EFFECT OF HANGMAN GAME TOWARD STUDENTS’ VOCABULARY MASTERY AT THE EIGHTH GRADE OF SMP BERDIKARI CIJAKU LEBAK – BANTEN - Titi Purwanti; Ade Sudirman; Rohimajaya, Nur Azmi (Al-Shobar Publisher, Yayasan Islam Al-Shobar Rawaurip, 2023)
This research paper aims to investigate a significant effect of Hangman game towards Students’ Vocabulary Mastery at the Eighth Grade of SMP Berdikari Cijaku Lebak-Banten in Academic Year 2022/2023. The research paper used the quantitative research. This research was conducted from August-September, and the researcher has chosen two classes are a control class and an experimental class. The technique in choosing the sample is purposive sampling; the researcher used VIII A (27 students) as class experimental and VIII B (27 students) as class control. The experimental group was taught used hangman game, where as the control group was taught used Bingo game. In the Collecting data technique, the researcher gives pre-test and post-test. The score pre-test of control group are 1.498, the score pre-test of experimental class are 1.688. Then, the score post-test of control group are 1.520, the score post-test of experimental group are 1.702. In analyzing the data, the researcher used SPSS statistical computation and used the result of the post-test both class control and experimental to analyze the hypotheses test. The researcher has found the result of Significant two-tailed = 0.000 < α 0.05. Therefore, the researcher concluded that the usage of hangman game has a significant impact on students’ vocabulary mastery in SMP Berdikari Cijaku, Lebak Banten.